2016
DOI: 10.1103/physrevb.94.045439
|View full text |Cite
|
Sign up to set email alerts
|

Epitaxially stabilized iron thin films via effective strain relief from steps

Abstract: We show a new way to stabilize epitaxial structures against transforming bulk stable phases for Fe thin films on a vicinal Cu(001) surface. Atomically-resolved observations by scanning tunneling microscopy reveal that high-density Cu steps serve as strain relievers for keeping epitaxially-stabilized Fe fcc(001) lattice even at a transient thickness towards the bulk stable bcc(110) lattice. Spectroscopic measurements further clarify the intrinsic electronic properties of the fcc Fe thin film in real space, impl… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 29 publications
0
9
0
Order By: Relevance
“…Indeed, the d I/ d V spectra of Mn(0, 3, 5)/Fe thin film heterostructures exhibit several electronic states near the Fermi level, especially the peak structure that commonly appears at ≈−0.2 eV. Note that this peak structure of Mn(5)/Fe thin film heterostructure, the pure fct Mn surface, originates from the out‐of‐plane‐oriented 3normald3z2r2 orbital . Accordingly, the peak of Mn(3)/Fe thin film heterostructure, the ordered FeMn alloy, at ≈−0.2 eV, is expected to have the same origin.…”
Section: Resultsmentioning
confidence: 98%
See 2 more Smart Citations
“…Indeed, the d I/ d V spectra of Mn(0, 3, 5)/Fe thin film heterostructures exhibit several electronic states near the Fermi level, especially the peak structure that commonly appears at ≈−0.2 eV. Note that this peak structure of Mn(5)/Fe thin film heterostructure, the pure fct Mn surface, originates from the out‐of‐plane‐oriented 3normald3z2r2 orbital . Accordingly, the peak of Mn(3)/Fe thin film heterostructure, the ordered FeMn alloy, at ≈−0.2 eV, is expected to have the same origin.…”
Section: Resultsmentioning
confidence: 98%
“…The electronic and magnetic properties of fcc Fe thin films on Cu(001) are quite sensitive to the changes in the lattice constant . Especially, the out‐of‐plane magnetic anisotropy emerges due to the expansion of the interlayer spacing between the top two layers relative to that in the inner layers of 1.78 Å .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Still no obvious difference in the terrace width is observed between the surfaces annealed at 900 and 1030 °C. Thus, the role of high-density steps acting as strain relievers to stabilize the surface lattice 18 is minor, and the annealing at an optimized temperature is essential for the formation of the p (1 × 1) lattice. Note that each LEED pattern is measured immediately after the STM observations, and thus a degradation of the surface can be excluded as a possible origin of the change in the LEED pattern 14 .…”
Section: Resultsmentioning
confidence: 99%
“…As one of promising approaches to stabilize the epitaxial lattice in this system, the authors group have recently proposed an important role of atomic steps acting as strain relievers. 20) Atomically resolved observations by scanning tunneling microscopy (STM) demonstrated that the strain relief from the step edges is effective on narrow Cu terraces, successfully stabilizing the fcc lattice of 7 ML Fe thin films on the whole terrace. For the region far from the step edges on wide Cu terraces, the bulk stable bcc(110) lattice and surface reconstructions with high-density adsorbates are additionally observed presumably due to the less effective strain relief mechanism in this region.…”
Section: Introductionmentioning
confidence: 99%